PENGARUH KOMPENSASI MANAJEMEN, CORPORATE GOVERNANCE, REPUTASI AUDITOR TERHADAP MANAJEMEN PAJAK (Studi Empiris pada Perusahaan Perbankan yang terdaftar di BEI Tahun 2011-2014) - Meiliza Celara Angela Putri; Zirman '; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aim of this study is to examine of management compensation, corporate governance and auditor reputation the influence on tax management. Besides that, this study also to examine the size of the company, debt ratio and corporate performance as the control variables the influence on tax management. The samples in this research are banking companis listed in Indonesia Stock Exchange (BEI) in 2011-2014. The sampling method use a purposive sampling method. Banking companies listed on the BEI in 2011-2014 amounted 42 companies. Companies that fit the criteria of research sample amounted to 16 companies. With 4 years observation period for the sample amounted to 64 samples. The method of analysis is multiple regression wtih using SPSS program. The partial regression test (t test) proves that the management compensation, corporate governance and auditor reputation which has and significant positive effect on tax management. Besides that, the debt ratio and corporate performance as the control variables which has and significant positive on tax management. While the size of the company as the control variables which has a not significant influence on tax management. The adjusted coefficient of determination (Adjusted R2) shows that 63.4% of the variation of tax management can be explained by the independent variables and control variables, while the remaining 36,6% is explained by other variables that do not exist in this study.Keyword: management compensation, corporate governance, tax management, auditor reputation